Invisibility as Power Forms, Role, Reaction of Exploitation in H.G. Wells’ The Invisible Man - Nata, Hasna; Ruly Indra Darmawan (LPPM Universitas Advent Indonesia, 2025)
Exploitation involves treating someone unfairly for personal gain or utilizing something to gain an advantage. This research explore the theme of exploitation in H.G Wells' The Invisible Man through a marxist literary lens, focus on three main findings: Griffin's exploitation of others through dehumanization and intrumentalization of labor, his dual role as both a victim and an agent of exploitation, and the social reactions to his actions, particularly in the forms of fear and resistance. Using a qualitative descriptive method, this research chose selected excerpts and interpreted them within the framework of Marxist theory. This analysis reveals how Griffin, a scientific genius who becomes a tool for domination, reducing others to mere instruments for his personal gain. At the same time, he also plays both roles as victim and agent of exploitation. At the end, this study reveals how society responds to Griffin's actions throughout the story, showing how fear can evolve into resistance when oppressive power threatens social stability. These results highlight Wells' critique of the capitalist exploitation of human potential as well as the complicated relationship between fear, resistance, and power in modern society.